2005
DOI: 10.1080/18811248.2004.9726441
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Isotope Separation by Plasma-Chemical Method

Abstract: Deuterium transfer (exchange) reaction as shown in HDO+H 2 =H 2 O+HD was studied as a case similar to the tritium transfer reaction as shown in DTO+D 2 =D 2 O+DT, the first step in tritium isotope separation of the tritiated heavy water DTO. The transfer reaction was plasma-chemically catalyzed by allowing a gas mixture such as H 2 O/D 2 , D 2 O/H 2 , H 2 O/HDO/H 2 or H 2 O/D 2 O/HDO/H 2 to flow through an atmospheric pressure discharge zone formed in a reaction chamber, the inner temperature of which was main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The ready recombination of H 3 O þ species will make it hard to sustain the discharge through atmospheric pressure water vapor. However, our previous study 1) revealed that AC powered MHC discharge in atmospheric pressure water/ hydrogen gas mixture was stabilized although it showed oscillatory current profile. Thus, we adopted MHC configuration as the electrode geometry to induce the discharge in pure water vapor at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The ready recombination of H 3 O þ species will make it hard to sustain the discharge through atmospheric pressure water vapor. However, our previous study 1) revealed that AC powered MHC discharge in atmospheric pressure water/ hydrogen gas mixture was stabilized although it showed oscillatory current profile. Thus, we adopted MHC configuration as the electrode geometry to induce the discharge in pure water vapor at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 88%
“…The details of the experiments, particularly the geometric configurations of the electrode and the spectroscopic setup, are described elsewhere. 1,12) The micro-hollow electrodes assembly for generating atmospheric pressure water plasma is shown in Fig. 1(a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of methods for the separation of hydrogen isotopes, such as by means of palladium membranes (1)(2)(3)(4)(5), gas chromatography (6)(7)(8)(9), pressure swing adsorption (10,11) and plasma-chemical reaction (12), have been reported. Among them, the first method is potentially competitive with other methods for small and intermediate scale applications (13).…”
Section: Introductionmentioning
confidence: 99%